PENGARUH PENGUSANGAN CEPAT DENGAN PERENDAMAN ETANOL TERHADAP VIABILITAS DAN VIGOR BEBERAPA BENIH PADI (Oryza sativa L.) - Rahayuningsih, Tri; Suryanto, Agus; Sulistyaningrum, Dyah Erlina (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
The availability of quality seeds is important in plant cultivation, so quality seeds must be available when farmers need them. Quality seeds must be able to be stored for a long time. Rapid aging by soaking in 95% ethanol for 5 minutes can estimate the shelf life of the seeds. The rice seeds treated with rapid aging are the Inpari 45 (V1), Sunggal (V2), Memberamo (V3) and Ciherang (V4) varieties. From the results of analysis of various observation parameters, Germination Power (DB), Maximum Growth Potential (PTM) and Growth Simultaneity (KST) differ very significantly (1%). Of the four varieties, after the seeds were soaked in 95% ethanol for 5 minutes DB, PTM and KST decreased very drastically. The order of varieties based on the level of seed viability and vigor, from high to low, is Inpari 45 (V1), Memberamo (V3) Sunggal (V2) and Ciherang (V4). The Inpari 45 (V1) variety has the highest germination capacity (DB), namely 39%, while the Ciherang variety (V4) has the lowest germination capacity (DB), namely 15.67%. From these results, it is suspected that the seeds of the Inpari 45 (V1) variety can be stored longer than the other three varieties. Apart from being controlled by environmental factors, seed viability and vigor are also influenced by genetic factors.